La censure des textes en Iran après la révolution de 1979 : histoire et fonctionnement - Nanquette Laetitia (Revue des Mondes Musulmans et de la Méditerranée)
This article traces the history of the contemporary censorship of literary texts in Iran and explains the operating of the censorship system after the Islamic Revolution. It discusses the evolutions of publishing politics and the impact of censorship on the Iranian literary field and on Iranian society with examples.